1989
DOI: 10.1101/gad.3.4.469
|View full text |Cite
|
Sign up to set email alerts
|

A nucleoprotein complex mediates the integration of retroviral DNA.

Abstract: The integration of viral DNA into the host genome is an essential step in the retrovirus life cycle. To understand this process better, we have examined the native state of viral DNA in cells acutely infected by murine leukemia virus (MLV), using both a physical assay for viral DNA and a functional assay for integration activity (Brown et al. 1987). The viral DNA and integration activity copurify during velocity sedimentation, gel filtration, and density equilibrium centrifugation, indicating that viral DNA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
262
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(270 citation statements)
references
References 30 publications
5
262
0
1
Order By: Relevance
“…The PIC is a macromolecular assemblage that consists of the viral cDNA, a subset of viral proteins retained from the initial reverse transcription complex, and probably host cell proteins [5,[15][16][17][18][19]. Similarly, chromatin is compositionally and structurally intricate.…”
Section: Host Cell Factors and Integrationmentioning
confidence: 99%
“…The PIC is a macromolecular assemblage that consists of the viral cDNA, a subset of viral proteins retained from the initial reverse transcription complex, and probably host cell proteins [5,[15][16][17][18][19]. Similarly, chromatin is compositionally and structurally intricate.…”
Section: Host Cell Factors and Integrationmentioning
confidence: 99%
“…We can now propose that this direction to the nucleus could be monitored by a NLS-like sequence (nucleotide position: 1079 to 1102 in the cDm2055 plasmid -see [36]); this sequence is found close to the nucleic acid binding site (nucleotide position 1123 to 1165 ), suggesting similar structural organisations in the Gag products of both copia and 1731. It has also been reported that the Gag product of Moloney Leukemia Virus was associated with the nucleoprotein complex involved in the process of transposition [37]. In addition the localization of Gag protein of foamy viruses was found to be nuclear, a localization due to the presence of glycine-arginine rich boxes (NLS-like) in its sequence [14].…”
Section: Nuclear-localization Of a Gag Speciesmentioning
confidence: 99%
“…The mechanism by which the MLV PIC enters the nucleus remains unclear, and the requirement for mitosis for MLV but not for human immunodeficiency virus (HIV) nuclear import was supposed to be simply due to the large size of the MLV nucleoprotein complex (2,16). Nevertheless, neither the MLV nor the HIV PIC enters the nucleus by passive transport.…”
mentioning
confidence: 99%
“…Reverse transcription (RT) occurs in an intracellular complex made of cellular and viral proteins termed the preintegration complex (PIC) (2). During and after mitosis, the PIC penetrates the nuclear compartment and the viral DNA integrates, as recently shown, into the human host cell genome near the start of transcriptional units (48).…”
mentioning
confidence: 99%
See 1 more Smart Citation